Toward gender equality: A critical assessment of evidence on social safety nets in Africa - Peterman, Amber; Kumar, Neha; Pereira, Audrey; Gilligan, Daniel O. (International Food Policy Research Institute, 2019)
Over the last decade, social safety nets (SSNs) have rapidly expanded on the African continent, becoming a core strategy for addressing poverty and vulnerability, responding to shocks, increasing productivity, and investing in human capital. SSNs’ popularity among governments and other stakeholders has been bolstered by regional evidence showing that they are effective at combating poverty and food insecurity, increasing resilience and agricultural productivity, and improving the education and well-being of future generations (Bastagli et al. 2016; Garcia and Moore 2012; Handa et al. 2018; Hidrobo et al. 2018). By 2017, every country on the continent had at least 1 SSN, with the number ranging from 2 (Republic of the Congo and Gabon) to 56 (Burkina Faso), and the average country having 15 (Beegle, Coudouel, and Monsalve 2018).